Undesired Small RNAs Originate from an Artificial microRNA Precursor in Transgenic Petunia (Petunia hybrida) - Guo, Yulong (Public Library of Science, 2014)
Although artificial microRNA (amiRNA) technology has been used frequently in gene silencing in plants, little research has been devoted to investigating the accuracy of amiRNA precursor processing. In this work, amiRNAchs1 (amiRchs1), based on the Arabidopsis miR319a precursor, was expressed in order to suppress the expression of CHS genes in petunia. The transgenic plants showed the CHS gene-silencing phenotype. A modified 5′ RACE technique was used to map small-RNA-directed cleavage sites and to detect processing intermediates of the amiRchs1 precursor. The results showed that the target CHS mRNAs were cut at the expected sites and that the amiRchs1 precursor was processed from loop to base. The accumulation of small RNAs in amiRchs1 transgenic petunia petals was analyzed using the deep-sequencing technique. The results showed that, alongside the accumulation of the desired artificial microRNAs, additional small RNAs that originated from other regions of the amiRNA precursor were also accumulated at high frequency. Some of these had previously been found to be accumulated at low frequency in the products of ath-miR319a precursor processing and some of them were accompanied by 3′-tailing variant. Potential targets of the undesired small RNAs were discovered in petunia and other Solanaceae plants. The findings draw attention to the potential occurrence of undesired target silencing induced by such additional small RNAs when amiRNA technology is used. No appreciable production of secondary small RNAs occurred, despite the fact that amiRchs1 was designed to have perfect complementarity to its CHS-J target. This confirmed that perfect pairing between an amiRNA and its targets is not the trigger for secondary small RNA production. In conjunction with the observation that amiRNAs with perfect complementarity to their target genes show high efficiency and specificity in gene silencing, this finding has an important bearing on future applications of amiRNAs in gene silencing in plants.